“Who Are the Rightful Inhabitants of this Earth?”: A Critical Analysis of Migration Representations and Border Practices (KULT_online, 2024)
Lilie Chouliaraki and Myria Georgiou critically explore the complexities of migration, power relations, and technology. They challenge dominant rationalities surrounding migration, proposing a nuanced understanding of borders as both territorial and symbolic. The authors’ self-reflexive approach and inclusion of migrant voices adds depth to the study. The book critiques recent theories on dehumanization and victimization, offering a multi-layered perspective on border practices.